The Effect of Muslim-Friendly Tourism on Muslim Tourist Satisfaction in Ciwidey District, Bandung Regency - Sari, Widya; Nur'aeni, Nur'aeni (Indonesian Journal of Economics and Management, 2023)
Halal tourism is a type of tourism that follows the teachings of the Islamic religion and has become popular in recent decades. It includes food, accommodation, and activities that comply with Sharia principles and aims to provide a more comfortable and safe travel experience for Muslim travelers. Halal tourism can also cater to the needs and preferences of Muslim travelers, thus increasing their travel satisfaction. In Bandung Regency, there are many potential objects to be used as halal tourism objects, especially since Bandung Regency has won an award as a Featured Halal Tourism Destination from the Ministry of Tourism. It is hoped that the halal market in Bandung Regency, generally Indonesia, will grow and develop, with local consumers becoming the main drivers of the halal tourism industry. The data used is primary data obtained from distributing questionnaires to respondents who visited the object of research. Data analysis was carried out through hypothesis testing in structural equation modeling (SEM) with the help of the WarpPLS application.